Meningkatkan hasil belajar pada tema diriku mengggunakan model pembelajaran make a match pada siswa kelas I - Salmah Riani (Persatuan Guru Republik Indonesia Kota Banjarbaru, 2021)
My learning theme at SDN Alalak Tengah 2 Banjarmasin is still below the individual KKM of 70. For this reason, it needs to be overcome by using the make a match learning model. This study aims to determine the activities of teachers and students in learning by using the make a match learning model and to find out the improvement in the learning outcomes of class I students at SDN Alalak Tengah 2 Banjarmasin by using the make a match learning model. This research was carried out in 2 cycles with the steps of planning, implementing, observing and reflecting. Each cycle is carried out in two meetings. The setting of the research was carried out in class I at SDN Alalak Tengah 2 Banjarmasin, totaling 32 students. Data collection using observation sheets and tests. The data were analyzed qualitatively and quantitatively, with indicators of success, namely an increase in teacher and student activities, as well as the achievement of individual and classical learning mastery. The results showed that learning activities increased from the first cycle with quite good criteria, in the second cycle it increased with very good criteria. Student activity experienced an increase in learning activity from being categorized as moderately active in the second cycle, increasing to the majority being very active. Classically, the 6 aspects observed also increased on average from cycle I to cycle II. Learning by using the make a match learning model can improve student learning outcomes. The conclusion of this study is that the teacher's activities in implementing the steps of the make a match learning model have met the criteria in the very good category. Student activities, both classical and individual, have met the criteria in the very active category. Student learning outcomes have met the criteria for completeness set both classically and individually.